Religion and civic engagement: the case of Iglesia ni Cristo in the Philippines - Serrano Cornelio, Jayeel (Religion, state & society, 2017)
The Iglesia ni Cristo (INC) is one of the fastest-growing indigenous Christian churches in the world. They have an estimated membership of 2.25 million adherents in more than 100 countries. In recent years its civic engagements have expanded through bigger relief operations and charity dedicated to the poor and those affected by calamities. These initiatives are typically articulated in terms of unity, duty and obedience to God. This article gives attention to this expansion by spelling it out and explaining it in view of its newfound role in civil society. This is an important intervention in the literature. Studies on INC have mainly focused on its successes in the political and religious spheres. INC now repackages itself as a civic organisation, which cares about public welfare. My argument is that this is how it manifests its new triumphalism in the Philippines, but with implications on its expanding presence in civil society.